Antitrichomonal activity of δ opioid receptor antagonists, 7-benzylidenenaltrexone derivatives. Issue 16 (15th August 2017) - Kutsumura, Noriki; Koyama, Yasuaki; Nagumo, Yasuyuki; Nakajima, Ryo; Miyata, Yoshiyuki; Yamamoto, Naoshi; Saitoh, Tsuyoshi; Yoshida, Naoko; Iwata, Satoshi; Nagase, Hiroshi
Graphical abstract: Abstract: The 7-benzylidenenaltrexone (BNTX) derivatives2a–v, 3a–c, 13a–c, and14a were synthesized from naltrexone (1 ) and evaluated for their antitrichomonal activity. The structure-activity-relationship studies found that 4-iodo-BNTX (2g ) showed the highest activity (IC50  = 10.5 µM) and the affinity for the opioid receptor was less important for antitrichomonal activity against Trichomonas vaginalis . The morphinan skeleton bearing both the double bond for a Michael acceptor and the phenolic hydroxy group would be a specific template for development of antitrichomonal agents. In addition, the mechanism of the antitrichomonal activity of the BNTX derivatives may differ from that of the standard drug, metronidazole.